Big data analytics in traffic and transportation engineering : emerging research and opportunities - Moridpour, Sara, 1980- (Engineering Science Reference, 2019)
"This book identifies the factors contributing to the severity of vehicle-pedestrian crashes at mid-blocks. It examines the influence of the socioeconomic factors of the neighborhoods where road users live (residency neighborhood) and where crashes occur (crash neighborhood) on vehicle-pedestrian crash severity, while controlling for the influences of roadway, road user, vehicle and environmental factors"--Provided by publisher
Keywords: Pedestrian accidents -- Australia -- Melbourne (Vic.) -- Statistical methods.; Traffic accidents -- Australia -- Melbourne (Vic.) -- Statistical methods.; Roads -- Interchanges and intersections -- Safety measures -- Statistical methods.; Big data -- Australia -- Melbourne (Vic.); elektronické knihy; electronic books